The Environmentalist and Development Value Paradox in Bangladesh: Case of Rampal Power Plant and the ‘Save Sundarbans’ Movement (Patan Pragya, 2021)
From the past decade, Bangladesh has shown a strong drive toward economic growth and in the process of achieving the related goal of becoming a middle-income country, it has adopted a power system plan that is heavily dependent on fossil fuels. As a result, there was a certain plan to build several coal powered plants, among which the most debated remains the plant initiated near the largest mangrove forest in the country, the Sundarbans. This power plant, called the Rampal power plant, has seen the emergence of a strong urban environmental movement resisting it. The anti-Rampal or ‘Save Sundarbans’ movement showcases the environment versus development discourses elaborately, with each side- the government and the environmental activists advancing their respective arguments supporting or opposing the plant under construction. This paper attempts to view these arguments through the lens of value theories, i.e. what are the values of either parties regarding the power plant and how they uphold these values. In a related vain, the environmentalist approach(s) of the movement are analyzed, as well as the development centered values of the state are analyzed within the energy/power sector context. Methods of critical discourse analysis were applied to analyze the public debate that ensued regarding the power plant.